Saliva proteomics updates in biomedicine - Katsani, Katerina R. (J Biol Res (Thessalon), 2019)
In the years of personalized (or precision) medicine the ‘omics’ methodologies in biomedical sciences—genomics, transcriptomics, proteomics and metabolomics—are helping researchers to detect quantifiable biological characteristics, or biomarkers, that will best define the human physiology and pathologies. Proteomics use high throughput and high efficiency approaches with the support of bioinformatic tools in order to identify and quantify the total protein content of cells, tissues or biological fluids. Saliva receives a lot of attention as a rich biological specimen that offers a number of practical and physiological advantages over blood and other biological fluids in monitoring human health. The aim of this review is to present the latest advances in saliva proteomics for biomedicine.